Body mass index and the prevalence, severity, and risk of coronary artery disease: an international multicentre study of 13 874 patients - Labounty, Troy M. (Oxford University Press, 2013)
AIMS: Obesity is associated with the presence of coronary artery disease (CAD) risk factors and cardiovascular events. We examined the relationship between body mass index (BMI) and the presence, extent, severity, and risk of CAD in patients referred for coronary computed tomographic angiography (CCTA). METHODS AND RESULTS: We evaluated 13 874 patients from a prospective, international, multicentre registry of individuals without known CAD undergoing CCTA. We compared risk factors, CAD findings, and risk of all-cause mortality and non-fatal myocardial infarction (MI) amongst individuals with underweight (18.5–20.0 kg/m(2)), normal (20.1–24.9 kg/m(2)), overweight (25–29.9 kg/m(2)), and obese (≥30 kg/m(2)) BMI. The mean follow-up was 2.4 ± 1.2 years with 143 deaths and 193 MIs. Among underweight, normal weight, overweight, and obese individuals, there was increasing prevalence of diabetes (7 vs.10% vs. 12 vs. 19%), hypertension (37 vs. 40% vs. 46 vs. 59%), and hyperlipidaemia (48 vs. 52% vs. 56 vs. 56%; P < 0.001 for trend). After multivariable adjustment, BMI was positively associated with the prevalence of any CAD [odds ratio (OR) 1.25 per +5 kg/m(2), 95% confidence interval (CI): 1.20–1.30, P < 0.001] and obstructive (≥50% stenosis) CAD (OR: 1.13 per +5 kg/m(2), 95% CI: 1.08–1.19, P < 0.001); a higher BMI was also associated with an increased number of segments with plaque (+0.26 segments per +5 kg/m(2), 95% CI: 0.22–0.30, P < 0.001). Larger BMI categories were associated with an increase in all-cause mortality (P = 0.004), but no difference in non-fatal MI. After multivariable adjustment, a higher BMI was independently associated with increased risk of MI (hazards ratio: 1.28 per +5 kg/m(2), 95% CI: 1.12–1.45, P < 0.001). CONCLUSIONS: Amongst patients with suspected CAD referred for CCTA, individuals with increased BMI have greater prevalence, extent, and severity of CAD that is not fully explained by the presence of traditional risk factors. A higher BMI is independently associated with increased risk of intermediate-term risk of myocardial infarction.